reyliruiz0670
reyliruiz0670
11-09-2020
Mathematics
contestada
f(n+1)=f(n)-3 f(1)=15
Respuesta :
samkr14
samkr14
11-09-2020
Answer:
f(n+1) = 13
Step-by-step explanation:
We know that f(1) = 15
So we can substitute this for f(n)-3
With this:
f(n+1) = f(1) -3
f(n+1) = 15-2
f(n+1) = 13
Answer Link
VER TODAS LAS RESPUESTAS ( 13+ )
Otras preguntas
Write an algebraic expression for “Julie runs three miles less than twice the number of miles, n, that Hannah runs.” A. 2n – 3 B. 3n – 2 C. 2n + 3 D. 3n + 2
what does the ntuser.dat file contain?
he is right it is setting it told me my answers and it was right
in government data, a household consists of all occupants of a dwelling unit. choose an american household at random and count the number of people it contains.
Given that K = √ 2 a b c 1 a 2 − b 2 c 2 − 5 b If a = 4 , b = − 2 and c = − 1 evaluate K
PLEASE HELP!! Show that quadrilateral ABCD is a parallelogram. Q(1,4) R(4,1) S(-1,-4) P(-4,-1)
In what pricing strategy are prices lowered in a series of steps with the demand by those who really desire the product being satisfied at the highest prices?.
Which statement describes meiosis?
“Solve the following systems of equations using any method” ( elimination, substitution, graphing)
Why does montag say that falling down in the middle of the street during his escape saved his life?.